New opportunities of the therapy of medicinal ophthalmic allergies - E. V. Jani; V. V. Pozdnyakova; K. E. Seliverstova (Российский офтальмологический журнал, 2018)
Drug allergy is one of the most common issues not only in ophthalmology, but in the general medicine. Drug-induced conjunctivitis is an inflammatory reaction of the conjunctiva, allergic or toxic, caused by the use of medicines. The frequency and severity of drug-induced conjunctivitis continuously increase as the arsenal of biologically active drugs increases. The purpose of the paper is to compare the efficacy of eye drops Opatanol (0.1 % olopatadine) and Vizallergol (0.2 % olopatadine) in the therapy of drug conjunctivitis. Materials and methods. Clinical observation involved 42 patients (26 women and 16 men) with drug conjunctivitis aged 28 to 56, which were divided into two groups. Group 1 (22 patients) received 2 drops of Opatanol twice a day, whill group 2 (20 patients) received 2 drops of Vizallergol once a day. The clinical observation included careful collection of history data, visometry andbiomicroscopy with the assessment of the condition of the eyelids and conjunctiva, taking into account the follicular reaction on a 3-point scale. Results. In the process of treatment, subjective sensations (itching, burning, discomfort) were found to gradually reduce in both clinical groups. The average duration of treatment in group 1 was 11 ± 0.1 days, in group 2 - 9 ± 0.3 days. Conclusion. The therapeutic effect of Vizallergol was somewhat higher than that of Opatanol, which is explained by a higher concentration of the main active substance, olopatadine. For citations: Jani E.V., Pozdnyakova V.V., Seliverstova K.E. New opportunities of the therapy of medicinalophthalmic allergies. Russian ophthalmological journal. 2017; 10 (3): 108-112. doi: 10.21516/2072-0076-2017-10-3-108-112 (in Russian).